The Organizational Socialization of Rural High School Principals: Teacher Influences - J. Casey Hurley (Journal of Research in Rural Education, 1992)
This article presents empirical findings from a recent study of how ten rural high school principals were socialized into instructional leadership roles. The data are analyzed in order to suggest ways to improve how principals are organizationally socialized in rural high schools.